2012
DOI: 10.1111/j.1600-065x.2012.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

IκB kinase regulation of the TPL‐2/ERK MAPK pathway

Abstract: Nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) activation play central roles in the induction of gene expression in innate immune cells following pathogen recognition. TPL-2 (tumor progression locus 2) is the MAP 3-kinase component of an ERK-1/2 (extracellular signal-regulated kinase 1/2) MAPK pathway activated by Toll-like receptor and tumor necrosis factor receptor family stimulation. In this review, we discuss results obtained from our laboratory and others that show that TPL-2 signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
145
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 130 publications
(246 reference statements)
6
145
0
4
Order By: Relevance
“…However, only high concentrations of LPS triggered delayed ERK1/2 activation (20 min after stimulation) by comparison with the C5a response, which occurs within 5 min. The MAP3K tumor progression locus 2 is essential for activation of ERK1/2 by multiple TLRs, including TLR4, in macrophages (44). Consistent with this, we observed that LPS triggered MEK1 phosphorylation in macrophages independently of activation of another MAP3K, c-Raf.…”
Section: Discussionsupporting
confidence: 76%
“…However, only high concentrations of LPS triggered delayed ERK1/2 activation (20 min after stimulation) by comparison with the C5a response, which occurs within 5 min. The MAP3K tumor progression locus 2 is essential for activation of ERK1/2 by multiple TLRs, including TLR4, in macrophages (44). Consistent with this, we observed that LPS triggered MEK1 phosphorylation in macrophages independently of activation of another MAP3K, c-Raf.…”
Section: Discussionsupporting
confidence: 76%
“…Tpl2 is currently considered a well-established inflammatory mediator, with significant pharmacological interest for IBD (3). We have shown a relevant pathogenic implication of Tpl2 in Tnf ΔARE mice which spontaneously develop a chronic T-cell-mediated Crohn's-like IBD pathology in the ileum (7) without involvement of epithelial barrier disruption and restoration processes in which IMFs could play an important homeostatic role.…”
Section: Discussionmentioning
confidence: 95%
“…S1 A and B). Molecularly, Tpl2 is known to bind to NF-ĸB1-p105 in a stabilized but inactive form (3) and, when activated, is released to phosphorylate the major immediate targets MEK1/2 activating mainly the ERK pathway and downstream inflammatory mediators (3). The NFKB1 gene is also genetically associated with IBD in GWAS (2), highlighting the relevance of this pathway to human disease.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Because sorafenib treatment rather resulted in increased Erk activation, it is unlikely that Raf kinases are involved in activation of this signaling pathway. It might be that PI3K/Akt is acting through the IKK complex to activate Mek and Erk because links between PI3K and NF-kB as well as NF-kB and MAPK-signaling have already been described (27,29).…”
Section: Discussionmentioning
confidence: 99%